Risk Factors of Interpersonal Violence in South Punjab: An Empirical Analysis - Madiha Riaz; Muhammad Ali Tarar; Javeed Iqbal; Amina Hanif Tarar (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Since centuries women are victim of violence in different ways. Several reasons have been attributed to it and several suppression methods have been introduced, yet domestic violence is still prevalent in South Asian countries generally and in underprivileged regions within the country specifically. This study analyzed the factors attributed to interpersonal violence (IPV) in the South Punjab as a Dera Ghazi Khan Division case study. Through primary survey analysis, 259 sample data was collected. By applying Univariate and multivariate techniques, study finds out that psychological violence is more dominant and prevailing in the region than physical violence, which is due to the backwardness of partner and their family backgrounds. The family status of respondent, her education, and income profile were insignificant in the study in reducing the violent act against her. Hence, it is suggested that instead of instruction to the women and campaigning for woman’s rights, male partners should be offered the education and knowledge to provide due rights to women. Moreover, the society norms should be restructured in favor of woman’s esteem, whether she is daughter or wife.